GAME EDUKASI ADAPTIVE LEARNING UNTUK MENINGKATKAN MINAT BELAJAR PEMROGRAMAN C++ BAGI MAHASISWA - Hudzaifah Nabil Amrullah; Adhi Rizal; Aji Primajaya (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2026)
C++ programming is a fundamental course in computer science education; however, its abstract nature and strict syntax lead to low student learning interest. Previous studies indicate that conventional learning approaches are one-size-fits-all and do not accommodate individual learning style differences. This study designs and implements an adaptive learning-based educational game called "Code Adventure" that integrates the Felder-Silverman Learning Style Model (FSLSM), Item Response Theory (IRT), and Dynamic Difficulty Adjustment (DDA) within the Unity 2D game engine. System development follows the Game Development Life Cycle (GDLC) with five stages: initiation, pre-production, production, testing, and release. Functionality testing employs black-box testing, while the effectiveness of learning interest improvement is measured through a pre-experimental one-group pretest-posttest design with convenience sampling of 19 students. Test results confirm that all adaptive learning features function according to specifications. N-Gain Score analysis yields an average value of 0.65 (medium category), indicating a significant improvement in C++ programming learning interest after using the adaptive educational game. These findings confirm that content personalization based on learning styles and dynamic difficulty adjustment can enhance student engagement and learning motivation